Pendidikan Keluarga Dalam Perspektif Tafsir Maudhu’i - Mizna Laila Albaar; Hasyim Haddade; Rahmi Damis (Jurnal Ilmiah Wahana Pendidikan, 2022)
Family education, also known as informal education, plays a very significant role in the process of developing a child's personality. Because it is in this family environment that children first receive a number of values ​​and norms that are instilled in them. Education in the family environment is the first and foremost education, so in family education it is expected to form children who have good personalities which can then be developed in subsequent educational institutions. to find out the thematic analysis of verses and the influence of the application of family education on children. A child has been prepared from the start so that at the age of puberty he is ready to carry out all the taklif that Allah has imposed on him, family education provides an understanding of the concept that the nature of a child must be developed through an Islamic education process.